Monoacylglycerol Lipase Inhibition Protects From Liver Injury in Mouse Models of Sclerosing Cholangitis. Issue 5 (30th December 2019) - Tardelli, Matteo; Bruschi, Francesca V.; Fuchs, Claudia D.; Claudel, Thierry; Auer, Nicole; Kunczer, Victoria; Baumgartner, Maximilian; A.H.O. Ronda, Onne; Verkade, Henk Jan; Stojakovic, Tatjana; Scharnagl, Hubert; Habib, Aida; et al.
Abstract : Background and Aims: Monoacylglycerol lipase (MGL) is the last enzymatic step in triglyceride degradation, hydrolyzing monoglycerides into glycerol and fatty acids (FAs) and converting 2‐arachidonoylglycerol into arachidonic acid, thus providing ligands for nuclear receptors as key regulators of hepatic bile acid (BA)/lipid metabolism and inflammation. We aimed to explore the role of MGL in the development of cholestatic liver and bile duct injury in mouse models of sclerosing cholangitis, a disease so far lacking effective pharmacological therapy. Approach and Results: To this aim we analyzed the effects of 3, 5‐diethoxycarbonyl‐1, 4‐dihydrocollidine (DDC) feeding to induce sclerosing cholangitis in wild‐type (WT) and knockout (MGL −/− ) mice and tested pharmacological inhibition with JZL184 in the multidrug resistance protein 2 knockout ( Mdr2 −/− ) mouse model of sclerosing cholangitis. Cholestatic liver injury and fibrosis were assessed by serum biochemistry, liver histology, gene expression, and western blot characterization of BA and FA synthesis/transport. Moreover, intestinal FAs and fecal microbiome were analyzed. Transfection and silencing were performed in Caco2 cells. MGL −/− mice were protected from DDC‐induced biliary fibrosis and inflammation with reduced serum liver enzymes and increased FA/BA metabolism and β‐oxidation. Notably, pharmacological (JZL184) inhibition of MGL ameliorated cholestatic injury in DDC‐fed WT mice and protected Mdr2 −/− mice from spontaneous liver injury, with improved liver enzymes, inflammation, and biliary fibrosis. In vitro experiments confirmed that silencing of MGL decreases prostaglandin E2 accumulation in the intestine and up‐regulates peroxisome proliferator–activated receptors alpha and gamma activity, thus reducing inflammation. Conclusions: Collectively, our study unravels MGL as a metabolic target, demonstrating that MGL inhibition may be considered as potential therapy for sclerosing cholangitis.